ANTIBACTERIAL ACTIVITY OF ANASTATICA HIEROCHUNTICA L.â€ AGAINST SOME BACTERIAL STRAINS RESPONSIBLE FOR WOMEN'S URO-GENITAL INFECTION - Benyagoub, Elhassan; Nabbou, Nouria; Razni, Dalila; Moghtet, Snoussi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The purpose of this work is to study the biological activity of Anastatica hierochuntica L., against nine bacterial strains responsible for women's uro-genital infection (UGI). Methods: The plant was collected from Tindouf region (far southwest Algeria). In this study, we performed an evaluation of antibacterial activity of three macerates of two vegetative parts (seeds and stems) by two methods (disc and wells diffusion methods), with a description of the antibiotic resistance profile of isolated bacterial strains by antibiogram method. Results: According to the results, the antibiotic resistance profile of the tested bacterial strains showed an increased resistance against several antibiotics families. The evaluation of the antibacterial potential of macerates showed that methanolic and aqueous macerates of the seeds were more active against Gram-positive bacteria compared to Gram-negative bacteria. Conclusion: The preliminary results of this study allowed us to predict that natural substances in the plant can be considered as an important source to possess compounds with significant antibacterial properties and thus suggest their application in the pharmaceutical industry.